HOW LIFESTYLE, CAFE ATMOSPHERE SHAPE, AND CUSTOMER EXPERIENCE AND REVISIT INTENTION AMONG GEN Z: EVIDENCE FROM TOMORO COFFEE SUMBAWA - Muhammad Nur Fietroh; Nurasia Nurasia; Hartini Hartini; Jayanti Mandasari; Joti Aprilia (Prosiding Seminar Nasional dan Call Paper STIE Widya Wiwaha, 2025)
This study aims to examine the impact of lifestyle, café atmosphere, and customer experience on revisit intention to Tomoro Coffee among Generation Z in Sumbawa. The sampling technique used in this study is purposive sampling, where the selected sample consists of Generation Z individuals residing in Sumbawa who have made repeat purchases at Tomoro Coffee.  The research method applied is quantitative with an associative approach, aiming to identify the relationship between independent and dependent variables. The data analysis technique used in this study includes multiple linear regression, classical assumption tests (normality test, multicollinearity test, and heteroscedasticity test), and hypothesis testing to determine the significance of relationships between variables.  The study results indicate that lifestyle, café atmosphere, and customer experience significantly influence revisit intention to Tomoro Coffee. The findings reveal that in Sumbawa, customer preferences prioritize comfort and location accessibility over mere menu aesthetics.  Furthermore, the coffee consumption trend among Generation Z continues to grow, influenced by social media and the adoption of an urban lifestyle in the region. This highlights that innovation in customer experience and digital marketing strategies has great potential to enhance customer loyalty at Tomoro Coffee.